2018
DOI: 10.1371/journal.pone.0191894
|View full text |Cite
|
Sign up to set email alerts
|

Motor and psychosocial impact of robot-assisted gait training in a real-world rehabilitation setting: A pilot study

Abstract: In the last decade robotic devices have been applied in rehabilitation to overcome walking disability in neurologic diseases with promising results. Robot assisted gait training (RAGT) using the Lokomat seems not only to improve gait parameters but also the perception of well-being. Data on the psychosocial patient-robot impact are limited, in particular in the real-world of RAGT, in the rehabilitation setting. During rehabilitation training, the Lokomat can be considered an “assistive device for movement”. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
1
13
1
Order By: Relevance
“…Standardized tests to evaluate the psychosocial impact in patients with SCI following robot-assisted training are lacking. Furthermore, the application of the Psychosocial Impact of the Assistive Device Scale (PIADS) on a sample of 10 patients demonstrated the benefits of training with Lokomat in patients with an impaired walking motor on the psychological aspect in addition to the motor benefits [ 51 ]. The absence of daily activity, and non-involvement in social life lead to depression, alcohol addiction and suicide [ 1 ].…”
Section: Sci-associated Complicationsmentioning
confidence: 99%
“…Standardized tests to evaluate the psychosocial impact in patients with SCI following robot-assisted training are lacking. Furthermore, the application of the Psychosocial Impact of the Assistive Device Scale (PIADS) on a sample of 10 patients demonstrated the benefits of training with Lokomat in patients with an impaired walking motor on the psychological aspect in addition to the motor benefits [ 51 ]. The absence of daily activity, and non-involvement in social life lead to depression, alcohol addiction and suicide [ 1 ].…”
Section: Sci-associated Complicationsmentioning
confidence: 99%
“…Three studies qualitatively assessed the expectations and experiences of pediatric patients affected by cerebral palsy and families regarding the use of Lokomat [41][42][43], and gathered positive results about the acceptability of the therapy. One study reported that the technology, as delivered in an in-patient setting, may have a positive psychosocial impact [40]. According to a study carried out in Colombia, most of the patients that use Lokomat as a rehabilitation therapy feel comfortable (47%), very safe (68%) and have a perspective of significant results with the therapy (68%).…”
Section: Discussionmentioning
confidence: 99%
“…Although in the literature studies, evaluating the ergonomic aspects of rehabilitation health technologies is progressively increasing [37], only a few are those are related to robotic devices for neurorehabilitation that also take into account both the physiotherapist and the patient [38,39]. Even rarer are in-depth analyses of these aspects in the pediatric field [40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, longer duration of the exercise sessions and a higher training intensity can be achieved. [7][8][9][10][11] To date, this innovative approach has not been applied in cardiovascular rehabilitation training, despite its great potential to counteract the deconditioning experienced by patients with symptomatic chronic heart failure. The aim of this pilot study was to investigate the safety, feasibility, and tolerability of exoskeleton-type robotic-assisted mobilization protocols in patients with severe heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Robotic assistance can augment the effect of physical training by facilitating motor recovery, supporting balance and stability and thus improving exercise capacity to a greater degree than conventional, non‐assisted training. As a result, longer duration of the exercise sessions and a higher training intensity can be achieved 7–11 …”
Section: Introductionmentioning
confidence: 99%